Long Run Dynamic Relationships between Oil Prices, Exchange Rates, Stock Market and Interest Rate in Malaysia. - Sabariah Nordin; Afiruddin bin Tapa; Hamdan Al-Jaifi (International Journal of Supply Chain Management, 2018)
This study intends to identify the long run relationships between oil price, exchange rates, stock market and interest rate in the context of Malaysia. Weekly data from 1 January 2006 until 22 April 2018 were used. Unit root tests of ADF and PP reveal that all variables are non-stationary at level and become integrated and stationary at first differential series, hence ratify that these variables can be used for further long run investigation. An ARDL bound test and Johansen and Juselius cointegration test suggest the existence of actual long-run relationship between oil price, stock price index, exchange rate and interest rate in Malaysia. Results of Granger causality indicates the presence of unidirectional causality between oil prices and Malaysian stock market running from oil prices to the stock price index. Results also suggest that there is a presence of bi-directional causality between interest rate and oil prices which means causality is running from interest rate to oil prices and from oil prices to the interest rate. Lastly, the results also propose that there is an existence of uni-directional causality between exchange rate and oil prices, running from the exchange rate to the oil prices at 10 percent significance level. Even the results of wavelet coherence approach confirm long run relationships between the underlying variables.